Delairea aparadensis (Asteraceae, Senecioneae), the first native species of the genus in the Americas - Funez, Luís A.; Hassemer, Gustavo; Peroni, Nivaldo; Drechsler-Santos, Elisandro R. (Phytotaxa, 2021)
We describe a narrowly endemic new species of Delairea from the highlands of southern Brazil. It is the second species described in this previously monospecific genus that was endemic to Africa, and the first record of a native species of Delairea in the Americas. Delairea aparadensis differs from D. odorata by its deltoid leaves and capitulescences composed by cymes of 2–6 capitula. Additionally, the new species is classified as critically endangered using the IUCN criteria.